2011
DOI: 10.1097/ta.0b013e3182032f45
|View full text |Cite
|
Sign up to set email alerts
|

Thromboembolic Prophylaxis With Low-Molecular-Weight Heparin in Patients With Blunt Solid Abdominal Organ Injuries Undergoing Nonoperative Management: Current Practice and Outcomes

Abstract: In patients with solid abdominal organ injuries undergoing NOM, early use of LMWH does not seem to increase failure rates or blood transfusion requirements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 25 publications
2
55
0
1
Order By: Relevance
“…[10][11][12] Our study adds further support for the safety of early (< 48 h) initiation of LMWH for VTE prophylaxis in patients with blunt SOIs and no significant intracranial pathology. The overall rate of failure of NOM was very low in this study, and suggests we are correctly identifying appropriate patients for a trial of NOM.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…[10][11][12] Our study adds further support for the safety of early (< 48 h) initiation of LMWH for VTE prophylaxis in patients with blunt SOIs and no significant intracranial pathology. The overall rate of failure of NOM was very low in this study, and suggests we are correctly identifying appropriate patients for a trial of NOM.…”
Section: Resultsmentioning
confidence: 89%
“…The incidence of VTE was similar to that in other cohorts; however, all instances of VTE in this study were in patients receiving early rather than late chemical VTE prophylaxis. [10][11][12] Current guidelines highlight a lack of evidence for or against early initiation of chemical VTE prophylaxis in patients undergoing NOM of blunt SOIs and have in par ticular stressed the unique challenge of managing these patients. 8 A lack of evidence precluded recommendations on this specific patient population particularly regarding the timing of chemical VTE prophylaxis by the Eastern Association for the Surgery of Trauma.…”
Section: Resultsmentioning
confidence: 99%
“…3.9%, which is in line with previous studies that reported failed NOM in 3.1 to 7.0% of trauma patients with SOI. 13,[19][20][21] However, in another study from our institution that analyzed the management of blunt splenic injuries, failed NOM was observed in 21% of patients with highgrade injuries. 22 Of the 80 patients that received heparin early, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…15 On the other hand, Eberle et al, in their retrospective study including patients with SOI undergoing NOM, reported early LMWH administration in only 13.2% of included patients. 13 Not surprisingly, the median ISS and number of patients with severe TBI (AIS head ≥ 3) were significantly higher in patients with late compared to early heparin administration. The higher injury burden and potential TBI-related bleeding complications most likely delayed heparin administration in these patients.…”
Section: Rostas Et Al Reported Early Lmwh Administration (<72 Hours) mentioning
confidence: 90%
See 1 more Smart Citation